2014
DOI: 10.1371/journal.ppat.1004412
|View full text |Cite
|
Sign up to set email alerts
|

Exploitation of the Complement System by Oncogenic Kaposi's Sarcoma-Associated Herpesvirus for Cell Survival and Persistent Infection

Abstract: During evolution, herpesviruses have developed numerous, and often very ingenious, strategies to counteract efficient host immunity. Specifically, Kaposi's sarcoma-associated herpesvirus (KSHV) eludes host immunity by undergoing a dormant stage, called latency wherein it expresses a minimal number of viral proteins to evade host immune activation. Here, we show that during latency, KSHV hijacks the complement pathway to promote cell survival. We detected strong deposition of complement membrane attack complex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(70 citation statements)
references
References 73 publications
2
66
2
Order By: Relevance
“…However, IL-6 primarily activates the STAT3 pathway (59). We did not observe any significant change in STAT3 phosphorylation during primary KSHV infection, although STAT3 is implicated in KSHV latent infection (60,61) and can be activated by KSHV vIL6, RTA, vGPCR (ORF74), and kaposin B, as well as through complement activation (61)(62)(63)(64)(65). In contrast to that of JAK1/2, the phosphorylation level of STAT5A was significantly reduced.…”
Section: Figcontrasting
confidence: 63%
“…However, IL-6 primarily activates the STAT3 pathway (59). We did not observe any significant change in STAT3 phosphorylation during primary KSHV infection, although STAT3 is implicated in KSHV latent infection (60,61) and can be activated by KSHV vIL6, RTA, vGPCR (ORF74), and kaposin B, as well as through complement activation (61)(62)(63)(64)(65). In contrast to that of JAK1/2, the phosphorylation level of STAT5A was significantly reduced.…”
Section: Figcontrasting
confidence: 63%
“…Of interest, instead of inhibiting the innate immune pathways, KSHV appears to hijack the pathways to promote viral latency and cell survival. We have shown that KSHV hijacks the complement pathway to promote cell survival by downregulating cell surface complement regulatory proteins CD55 and CD59 (13). Here, we have demonstrated that KSHV miRNA cluster, particularly miR-K1, -K3 and -K11, mediates the upregulation of TLR4 to induce chronic inflammation, and promote cellular transformation and tumorigenesis (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…ΔmiR cells stably expressing 12 individual pre-miRs (-K1 to -K12) were also grown under the same condition (20, 21). Telomerase-immortalized human microvascular endothelial cells (TIME) and KSHV-infected TIME cells (TIME-KSHV) were maintained as previously described (13). All cell lines were routinely tested for mycoplasma contamination using LookOut ® Mycoplasma qPCR Detection Kit (Sigma MP0035–1KT).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…KCP is part of the virion and functions as a cofactor for factor I-mediated cleavage of C3b and C4b, the complement system's opsonizing factors (52,53). KSHV has also been reported to exploit the host complement system to promote viral persistent infection (54).…”
Section: Introductionmentioning
confidence: 99%